Three distinct developmental pathways for adaptive and two IFN-γ-producing γδ T subsets in adult thymus - Terkild Brink Buus (Nature Portfolio, 2017)
Mouse γδ T cells have diverse functional subsets, but how these subsets are programmed during their development is still unclear. Here the authors show that three surface markers, CD117, CD200 and CD371, refine the development of γδ T cells in the thymus into three pathways programming distinct γδ T cell subsets.